Bokashi-Based Home Composter for Fertigation System - Abdul Razak, Mohd Azhar; Najib, Iqbal; Mahmood, Nasrul Humaimi; Zakaria, Nor Aini; Mat Safri, Norlaili; Othman, Mohd Afzan; Eileen Su Lee Ming (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Organic waste management is a huge problem coming from residential homes throughout the country. Improper decomposition of waste generates methane, which contributes significantly to the environment in terms of greenhouse effects. The proposed solution is the Bokashi-Based Home Composter for Fertigation System as a medium of Internet of Things (IoT). This system is designed to help users initiate composting through Bokashi composting and automated fertigation. Bokashi composting involves using airtight containers, Bokashi bran, and organic waste, which undergoes anaerobic fermentation to produce Bokashi Tea - a liquid by-product used as a fertilizer. The system architecture features an ESP32 microcontroller, soil moisture, humidity, and temperature sensors, as well as pumps for dosing and irrigation, all controlled through an application dashboard. The final product assembly successfully achieved its objectives to produce Bokashi Tea in less than 14 days and utilize it by dosing it to water with ratio of 1:100 with flow a flow rate of 1.6 ml/s and main pump flow rate of 32.5 ml/s for fertigation purposes in residential homes. The system is complemented by an application dashboard that provides IoT functionality, where the hardware parameters can be monitored and controlled by the application through Wi-Fi connectivity. This paper explores the process of product design.